PENGALAMAN DAN MAKNA KLIEN KETERGANTUNGAN NAPZA SAAT FASE AWAL KETERGANTUNGAN DI KABUPATEN SLEMAN - Wahyu Hidayati, Rizqi; Winarni, Indah; Dewi Rachmawati, Septi (MEDIA ILMU KESEHATAN, 2017)
Background: Drug abuse has become a global problem, including in Indonesia, especially Yogyakarta. Yogyakarta is the province with the highest prevalence of drug abuse among students in Indonesia. Usage of drugs has a negative impact on health both physically and psychologically. However, based on preliminary studies, drug users continue to use the substance, althought they know its effect. The client experience of drug dependence when first trying the substance is interesting to look at. Objective: The aim of this study was to explore the experiences of the pearticipant in their early stage of drug addiction in Sleman Regency. Methods: The study method used qualitative with design of phenomenology intepretif, and use method of IPA as method of data analysis. Results: Based on the results of the analysis of the phenomenology intepretif of the 9 participants obtained the theme of the results are as follows: Trying to be part of the world of drugs and drug self-control. Conclusion: Someone uses drugs due to various things one of them improves self-existence. For future research is expected to take place at BNN or hospital to see a different experience. Keywords: Drug abuse, initial phase of drug abuse